CONTRASTIVE LINGUISTICS FOR LANGUAGE ACQUISITION AND LEARNING: AN ANALYTICAL STUDY - DreAroua Nedjar (International Journal of Innovative Technologies in Social Science, 2025)
The analysis carried out by contrastive linguistics helps to extract the similarities and differences between two languages, particularly in contact, and above all, in a learning environment of the target language in the presence of the mother tongue. This discipline endeavours to propose solutions to ensure good language acquisition. The aim is not only to deduce the convergences and divergences between two languages but also, and above all, to extract the difficulties encountered by language learners and find solutions to enrich this learning, i.e. to envisage appropriate teaching strategies.